1996
DOI: 10.1017/s0890060400001633
|View full text |Cite
|
Sign up to set email alerts
|

Function–behavior–structure paths and their role in analogy-based design

Abstract: In many creative design processes, cross-domain knowledge is required to inspire the new design result. Thus, in knowledge-based design, how we represent the cross-domain knowledge becomes a key issue. In this paper, we present a formalism for design knowledge representation. By analyzing function representation in different design domains, from graphic design and industrial design to architectural and engineering device designs, we find that although the focus of each kind of design is different, the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
134
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(135 citation statements)
references
References 8 publications
1
134
0
Order By: Relevance
“…A graph grammar representation however encodes much more complex forms of functioncomponent mapping by using grammar rules. Previous work on computational design synthesis for product assemblies using graph grammar representation [15] describes a two layer approach as a simplification of the Function Behavior Structure approach [16]. This uses function structure and a Component Flow Graph to represent electromechanical products such as compressors, blowers, hair dryer etc.…”
Section: Related Workmentioning
confidence: 99%
“…A graph grammar representation however encodes much more complex forms of functioncomponent mapping by using grammar rules. Previous work on computational design synthesis for product assemblies using graph grammar representation [15] describes a two layer approach as a simplification of the Function Behavior Structure approach [16]. This uses function structure and a Component Flow Graph to represent electromechanical products such as compressors, blowers, hair dryer etc.…”
Section: Related Workmentioning
confidence: 99%
“…To represent the relations between product functions and physical structures, Kusiak et al used a rule-based system to decompose customer requirements and functions, to map requirements to functions, and to record alternative solutions (Kusiak et al 1991); other researchers identified the necessity of using part behavior to bridge the gap between abstract functions and physical objects (Welch and Dixon 1992;Umeda et al 1996;Qian and Gero 1996). Their researches indicate that product functions represent by part behaviors model deeper design knowledge than geometry, topology, parameters, and constraints.…”
Section: Engineering Intent Representation and Managementmentioning
confidence: 99%
“…Qian and Gero [23] show how analogy-based design can be implemented using the Function-Behavior-Structure (FBS) knowledge representation. They claim that the FBS path connecting function with behavior, and behavior with structure is the key to analogy in design.…”
Section: Related Workmentioning
confidence: 99%